IDENTIFICATION OF CYCLOPROPYL FATTY ACIDS IN WALNUT (JUGLANS REGIA L.) OIL - Hanus, Lumir Ondrej; Goldshlag, Paulina; Dembitsky, Valery Mikhail (Biomedical papers, 2008)
Aim: Identification of cyclopropyl fatty acids in walnut oil.Method: GC/MS method was developed for the determination of eight cyclopropyl fatty acids in walnut (Juglans regia) oil.Results: Monocyclopropane acids: methyl 9-cyclopropyl-nonanoate, 6,7-methylene-, 8,9-methylene-, 9,10-methylene-, 11,12-methylene octadecanoates, and dicyclic acid - methyl 9,10,12,13-dimethylene octadecanoate, tricyclic acid - methyl 9,10,12,13,15,16-trimethylene octadecanoate, and unsaturated - methyl 2-octylcyclopropene-1-octanoate were detected in walnut oil by GC-MS and their mass spectra studied. Four cyclic fatty acids were identified for the fist time in seed oils.Conclusions: Eight cyclopropyl fatty acids were detected in the Mediterranean nuts for the first time.
Keywords: GC-MS/Cyclopropyl acids/Walnut oil/Sunlight exposure